Portfolio allocation in the face of a means-tested public pension - Deborah A. Cobb-Clark; Vincent A. Hildebrand (Institute for the Study of Labor (IZA), 2009)
Is there evidence that households adjust their asset portfolios just prior to retirement in response to a means-tested public pension? We address this question by estimating a system of asset equations constrained to add up to net worth. We find little evidence that in 2006 healthy households or couples responded to the incentives embedded in the means test determining pension eligibility by reallocating their assets. While there are some significant differences in asset portfolios associated with being near the income threshold, being of pensionable age, and being in poor health these differences are often only marginally significant, are not robust across time, and are not clearly consistent with the incentives inherent in the pension eligibility rules. In 2006, any behavioral response to the means test seems to occur among single pensioners in poor health. Comparison with 2002 results suggests the incentives to reallocate assets may have weakened over time.
urn:nbn:de:101:1-20091019305
Keywords: H30; H31; D31; 330; Asset portfolios; means testing; public pension; household wealth; Gesetzliche Rentenversicherung; Bedarfsprinzip; Altersgrenze; Alte Menschen; Anlageverhalten; Portfolio-Management; Australien